Effectiveness and safety of systemic therapy for moderate-to-severe atopic dermatitis in children and adolescent patients: a systematic review - Zheng, Yu; Ding, Rui-Lian; Bu, Jin (Frontiers in Immunology, 2024)
EVIDENCE REVIEW On Feb 29, 2024, a systematic literature search was conducted in Embase, PubMed, and the Cochrane Central Register of Controlled Trials (Central). No date restrictions were applied. Randomized clinical trials, cohort studies, large case series, and meta-analyses were assessed to evaluate the efficacy (or effectiveness) and/or safety of systemic treatments for moderate-to-severe atopic dermatitis in children and adolescents. FINDINGS A preliminary search yielded 1457 results, from which 19 unique articles with a total of 3741 patients were included in the analysis. Overall, the available data for each systemic medication are limited, and the overall quality of the included studies on conventional systemic treatments is relatively low. When Dupilumab was used as a standalone treatment, 30%-40% of infants and toddlers aged 6 months to 2 years achieved EASI-75, while 50% of patients aged 2 to 6 years achieved EASI-75. In children aged 6 to 12 years, 33.0%-59.0% of atopic dermatitis patients achieved EASI-75, and when combined with topical corticosteroids (TCS), 69.7%-74.6% achieved EASI-75. Long-term data showed EASI-75 rates ranging from 75.0% to 94.0% for this age group. For adolescents aged 12 to 18 years, 40%-71% of patients achieved EASI-75 within 12 to 16 weeks, and by week 52, 80.8% of patients achieved EASI-75.Abrocitinib treatment resulted in 68.5%-72.0% of patients achieving EASI-75. Omalizumab treatment at week 24 showed a percentage change in SCORAD scores of -12.4%. In the Methotrexate treatment group, there was a SCORAD change of -26.25% at week 12, while the Cyclosporine A group had a SCORAD change of -25.01%. Patients treated with IVIG (Intravenous Immunoglobulin) showed a -34.4% change in SCORAD percentage scores at week 4, which further decreased by 47.12% at week 24. Patients receiving 4mg of Baricitinib and TCS had a 52.5% rate of EASI-75 at 16 weeks, and patients receiving different doses of upadacitinib had a 63-75% rate of EASI-75 at 16 weeks. The rate of EASI-75 at 16 weeks was around 28% in patients who received various doses of Tralokinumab.The most common adverse events observed were nasopharyngitis, respiratory events and dermatitis atopic.